2015
DOI: 10.1614/ws-d-14-00147.1
|View full text |Cite
|
Sign up to set email alerts
|

ALS-Resistant Smallflower Umbrella Sedge (Cyperus difformis) in Arkansas Rice: Physiological and Molecular Basis of Resistance

Abstract: Smallflower umbrella sedge is a problematic weed in direct-seeded rice in the midsouthern United States. It recently has evolved resistance to the acetolactate synthase (ALS) -inhibiting herbicide halosulfuron in Arkansas rice. Studies were conducted (1) to determine if the resistant biotype is cross resistant to other ALS-inhibiting herbicides, (2) to evaluate alternative herbicide control options, and (3) to determine the mechanism of resistance. Whole-plant bioassay revealed that halosulfuronresistant plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 18 publications
4
21
0
Order By: Relevance
“…Plants were harvested, dried at 72°C for 48 h and measured for total above ground biomass. Biomass values were adjusted to the nonsprayed controls by dividing each individual by the average biomass of its population grown in the nonspray control treatment following standard protocols (Tehranchian et al 2015). At the time of sampling survival and biomass remaining post-herbicide (3 weeks after herbicide application), none of the plants exhibited signs of regrowth indicating that our measure of resistance does not confound resistance with tolerance (see Baucom & Mauricio 2008).…”
Section: Population Samplingmentioning
confidence: 99%
“…Plants were harvested, dried at 72°C for 48 h and measured for total above ground biomass. Biomass values were adjusted to the nonsprayed controls by dividing each individual by the average biomass of its population grown in the nonspray control treatment following standard protocols (Tehranchian et al 2015). At the time of sampling survival and biomass remaining post-herbicide (3 weeks after herbicide application), none of the plants exhibited signs of regrowth indicating that our measure of resistance does not confound resistance with tolerance (see Baucom & Mauricio 2008).…”
Section: Population Samplingmentioning
confidence: 99%
“…Calha et al [30] described cross-resistance to the SUs azimsulfuron, bensulfuron-methyl, cinosulfuron, and ethoxysulfuron, but not to imazethapyr (IMI) for A. plantago-aquatica populations collected in rice paddy fields in Portugal. Different patterns of cross-resistance to ALS-Inhibitors were also reported for Italian, North American, and Spanish populations of C. difformis [5,7,31,32], ranging from populations that are resistant only to SU to others cross-resistant to the SUs bensulfuron-methyl, halosulfuron-methyl, orthosulfamuron, imazethapyr (IMI), bispyribac-sodium (PB), penoxsulam (TP), and propoxycarbazonesodium (SCT) [7]. Similarly, previous studies reported S. mucronatus populations having different patterns of cross-resistance in Italy, USA and Chile [8,31,33]).…”
Section: Discussionmentioning
confidence: 60%
“…Pro197 to His is often associated to resistance to SU but low or moderate to IMI or TP, while Trp574 to Leu confers broad cross-resistance to different ALS-inhibitor groups [8,[33][34][35][36]. However, Pro197 to His has recently been detected in an American C. difformis population that is characterized by a cross-resistance to bispyribac-sodium (PB), halosulfuron (SU), imazamox (IMI), and penoxsulam (TP) [32], so the level of homozygosis for this point mutation in a given individual can probably influence the level and pattern of resistance to ALS-inhibitors. Since different levels of ploidy (diploid and tetraploid) have been reported for C. difformis [36][37][38], the existence of multiple copies of ALS genes could also contribute to modify the pattern and level of resistance conferred by a specific point mutation.…”
Section: Discussionmentioning
confidence: 99%
“…The authors [1,8] calculated the error ΔtPTS for a standard measuring circuit at different temperatures. Since our measurement scheme used a similar measuring potentiometric setting, we will use the results [5,8] to determine the error of temperature measurement. The data of temperature measurement errors are presented in table 3.4.…”
Section: Estimation Of Temperature Measurement Errormentioning
confidence: 99%
“…To estimate the random error, data on the measurement of specific volumes of water at six isotherms were used. The obtained values were compared with the literature data [8,9]. As an approximate estimate of the random error of our experimental data we can take the total for all isotherms estimate of the standard deviation of the measured specific volumes compared with the literature data:…”
Section: Evaluation Of Measurement Uncertainty Of Specific Volumementioning
confidence: 99%